A model for enhanced up-conversion luminescence in erbium-doped tellurite glass containing silver nanoparticles - Ghoshal, Sib Krishna (2012)
Nanoparticles (NPs) size dependent enhancement of the infrared-to-visible frequency up-conversion (UC) and absorption coefficient in silver NPs embedded Er3+ doped tellurite glasses on pumping with the 976 nm radiation are investigated. Rate equations are derived by developing a comprehensive 4-level model in integrating the effects of quantum confinement and local field of silver NPs. Considering the spherical NPs size distribution as Gaussian, an analytical expression for the luminescence intensity and absorption coefficient are obtained for the first time. An enhancement in UC emission intensity of the green bands (2H11/2?4I15/2 and 4S3/2?4I15/2) and red band (4F9/2?4I15/2) emission of Er3+ ion at temperature 250 K and at optimized Er3+ concentration 1.0 mol% is observed up to few times in the presence of silver NPs. Furthermore, the green emission shows larger enhancement than the red emission. The observed of Er3+ luminescence is mainly attributed to the local field effects namely the surface plasmon resonance of silver NPs that causes an intensified electromagnetic field around NPs, resulting in enhanced optical transitions of Er3+ ions in the vicinity. The model is quite general and can be applied to other rare earth doped glasses containing metallic NPs. Our results on NPs size dependent emission intensity and absorption coefficient are in conformity with other findings. The present systematic study provides useful information for further development of UC lasers and sensors.